Sistem Kalender Islam Dalam Perspektif Evolusi Syari’ah - Abd. Salam (Universitas Islam Negeri Mataram, 2008)
This article tries to read Mecca and Medina messages by referring to Mahmud Muhammad Thaha’s, a Sudanese writer, term that is syariah evolution of Islamic calendar system. Mecca messages commanding to seeing the sky are theological, while Medina messages are more practical aspects from Mecca messages which are implemented in setting Islamic calendar not only through ru’yah bi al-fi’l, but also by hisab or computing based on syar’i pillars. The obeyed syar’i pillars represent that the human computing result should be considered a symbol of flexible Islamic teachings. Considering that, this writing points to a certain positioning, that Islamic calendar does not have only theological edge (Mecca messages), but also cultural one (Medina messages). As a theological calendar, Islamic calendar setting should be framed with adherence to syar’i pillars. As a cultural calendar, its arrangement should be designed by following human civilization advancement in astronomy.